“Another university is possible?”: A Study of Indigenizing and Internationalizing Initiatives in two Canadian Postsecondary Institutions - Chatterjee, Soma; Shahrokni, Shirin; Gomez, Bianca; Poojary, Monisha (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2022)
The aspirational postsecondary strategies of Indigenizing and internationalization claim to address pressing political questions such as racism and systemic inequities in the university. Through close examination of these initiatives in two key postsecondary institutions in Toronto, Canada, we show how these priorities instead betray strategic investment in diversity in three specific ways: first, universities are positioned as a horizontal “community of changemaker” that are themselves disarticulated from global relations of inequities. Next, international and Indigenous students’ welcome is made conditional and contingent on their becoming “diversity informants” for the university and its normative membership. Related to that, the claims of curricular diversity reify established epistemic hierarchies. We end the article with some final reflections on the merits of reforming the university, discussing the tensions, and the limits and possibilities of this project.